REDUCING INEQUALITIES IN ACCESS TO LOGISTICS SERVICES: ALIGNING WITH SDG 10 IN UZBEKISTAN - Samariddin Makhmudov; Doniyar Karshiev (International Journal of Artificial Intelligence for Digital Marketing, 2024)
This paper explores the issue of inequalities in access to logistics services in Uzbekistan and examines how these disparities impact economic growth and social equity. It aligns with Sustainable Development Goal (SDG) 10, which aims to reduce inequality within and among countries. The paper analyzes the current state of logistics infrastructure and services, highlighting the disparities between urban and rural areas, as well as among different socio-economic groups. It discusses the factors contributing to these inequalities and proposes strategies to enhance accessibility and inclusivity in the logistics sector. By addressing these disparities, Uzbekistan can foster more equitable economic opportunities and support sustainable development